Lights for epilepsy: can photobiomodulation reduce seizures and offer neuroprotection? - Napoleon Torres-Martinez; Stephan Chabardes; John Mitrofanis (Neural Regeneration Research, 2023)
Epilepsy is synonymous with individuals suffering repeated “fits” or seizures. The seizures are triggered by bursts of abnormal neuronal activity, across either the cerebral cortex and/or the hippocampus. In addition, the seizure sites are characterized by considerable neuronal death. Although the factors that generate this abnormal activity and death are not entirely clear, recent evidence indicates that mitochondrial dysfunction plays a central role. Current treatment options include drug therapy, which aims to suppress the abnormal neuronal activity, or surgical intervention, which involves the removal of the brain region generating the seizure activity. However, ~30% of patients are unresponsive to the drugs, while the surgery option is invasive and has a morbidity risk. Hence, there is a need for the development of an effective non-pharmacological and non-invasive treatment for this disorder, one that has few side effects. In this review, we consider the effectiveness of a potential new treatment for epilepsy, known as photobiomodulation, the use of red to near-infrared light on body tissues. Recent studies in animal models have shown that photobiomodulation reduces seizure-like activity and improves neuronal survival. Further, it has an excellent safety record, with little or no evidence of side effects, and it is non-invasive. Taken all together, this treatment appears to be an ideal treatment option for patients suffering from epilepsy, which is certainly worthy of further consideration.